2018
DOI: 10.1002/jgh3.12044
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of non‐alcoholic fatty liver disease in Bangladesh

Abstract: Background and AimNon‐alcoholic fatty liver disease (NAFLD) is a significant cause of hepatic dysfunction and liver‐related mortality. As there is a lack of population‐based prevalence data in a representative sample of general population, we aimed to estimate the prevalence and risk factors of NAFLD in Bangladesh.MethodsA cross‐sectional study was conducted both in urban and rural areas of Bangladesh from December 2015 to January 2017. Data were collected using a pretested structured questionnaire followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 43 publications
7
40
0
3
Order By: Relevance
“…The prevalence was 71·2% (64·1-77·4) in people with diabetes and 63·6% (59·4-67·5) in obese individuals (BMI ≥27·50 kg/m²). 218 By comparison, a rural study in Bangladesh showed that the overall prevalence of NAFLD was 18·4% (12·4-25·6). 219 The prevalence of overweight, obesity, and diabetes in Bangladesh has increased in the past three decades, thus increasing the NAFLD-related liver disease burden.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 97%
See 1 more Smart Citation
“…The prevalence was 71·2% (64·1-77·4) in people with diabetes and 63·6% (59·4-67·5) in obese individuals (BMI ≥27·50 kg/m²). 218 By comparison, a rural study in Bangladesh showed that the overall prevalence of NAFLD was 18·4% (12·4-25·6). 219 The prevalence of overweight, obesity, and diabetes in Bangladesh has increased in the past three decades, thus increasing the NAFLD-related liver disease burden.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 97%
“…There have been substantial advances in research on liver diseases in Bangladesh and several epidemiological studies have been published in the past two decades. [56][57][58][59][60][61][62]149,150,[152][153][154][155][156][218][219][220]223,[406][407][408] Still, baseline data on incidence, prevalence, risk factors, natural history, and the changing epidemiology of various causes of liver diseases need to be generated. Studies are needed to develop cheap, accessible, point-of-care testing for HBV and HCV, and on preventive measures and new drug treatments for NAFLD.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…Being male is also a risk factor for NAFLD [26]. A number of studies have shown that the prevalence of NAFLD in males is higher than in females before the age of 50 [26,27,29]. Our study suggests that the prevalence of NAFLD in males is signi cantly higher than that in females in people younger than 60 years old.…”
Section: Discussionmentioning
confidence: 45%
“…43 According to the present study, higher income and higher educational levels were not risk factors for NAFLD. According to the two previous ndings, there was a statistically signi cant association of high-income level with NAFLD 5,38 and higher education with the NAFLD. 38 The diagnosis of the NAFLD mainly depended on the ultrasound scan.…”
Section: Discussionmentioning
confidence: 86%
“…According to the two previous ndings, there was a statistically signi cant association of high-income level with NAFLD 5,38 and higher education with the NAFLD. 38 The diagnosis of the NAFLD mainly depended on the ultrasound scan. The gold standard method to diagnose NAFLD was a liver biopsy.…”
Section: Discussionmentioning
confidence: 86%